Transformative Female Leadership: Solichah Wahid Hasyim's Contribution at Muslimat NU 1950-1994 - Agus Mahfudin Setiawan; Masrokah; Uswatun Hasanah (Universitas Nahdlatul Ulama Surabaya, 2025)
Muslimat Nahdlatul Ulama (NU) was established to enhance the role of Muslim women in religious, social, and educational spheres. As a key figure, Solichah Wahid Hasyim played a pivotal role in transforming Muslimat NU from its early form as Nahdlatul Oelama Moederbond (NOM) into an autonomous NU body with a clear organizational vision. Guided by transformative leadership theory and gender and development perspectives, this study examines her leadership strategies in institutionalizing Muslimat NU through the establishment of local branches, member capacity building, and program innovation. This study employs historical research methods encompassing four stages: heuristic (collecting archival records and treatises), source criticism (evaluating authenticity and credibility), interpretation (contextualizing contributions within Indonesia's socio-political landscape), and historiography (systematic narrative construction). The findings reveal that Solichah challenged the entrenched domestic stigma faced by women from Islamic boarding schools by initiating campaigns to eradicate illiteracy, promoting vocational training, and advancing health education, while aligning these initiatives with Islamic values. Her influence extended nationally through active participation in the Indonesian Women's Congress (KOWANI) and the national parliament, where she advocated for policies related to women's rights and education. This study underscores the importance of integrating religious legitimacy with transformative leadership to achieve sustainable women's empowerment. The findings not only enrich leadership and gender studies within the Islamic context but also highlight Solichah Wahid Hasyim's enduring legacy as a role model for contemporary Muslim women leaders in Indonesia.